PENGADMINISTRASIAN KEUANGAN DAERAH DAN DASAR-DASAR HUKUMNYA - Abdul Rahman (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2011)
Role of Local Government Revenues and Expenditure (APBD) or the Public Sector Budget become increasingly significant. In its development, budget policy has become a multi-function instrument that is used as a means to achieve regional development goals. This is particularly evident from the composition and size of the budget that directly reflects the direction and goals of service to the community. Therefore, for budget function may be optimized, then the budget system and records of its receipts and expenditures must be done carefully and systematically. As a system, budget management area has undergone many developments. With the release of three packages of legislation in the field of public finance, namely Law no. 17 of 2003 on State Finance, Law no. 1 / 2004 on State Treasury, and Law. 15 of 2004 on the Audit of the Management and Financial Responsibilities of the State, local budget management systemin Indonesia is constantly changing and developing in accordance with the dynamics of public sector management. The Government has implemented a performance-based budgeting approach, integrated budget and medium-term expenditure framework in the fiscal year 2005 and 2006. Apparently there are still many obstacles encountered, mainly due to the unavailability of adequate implementation of the regulations, so that multiple interpretations are still a lot happening in the implementation in the field. In that period also has issued various regulations, rules of finance ministers, director generals and so forth regulations to cover these weaknesses